WHAT DO NEOTROPICAL PRIMATES TELL US UNDER THE LOOK OF CYTOGENETICS? - Steinberg E.R.; Bressa M.J.; Mudry M.D. (BAG. Journal of Basic and Applied Genetics, 2022)
Cytogenetics studies in Neotropical Primates (Primates: Platyrrhini) have shown that these mammals comprise a heterogeneous group at the chromosomal level. The remarkable variety of karyotypes described provides significant evidence on the possible role of chromosomal rearrangements in their evolution. In the Grupo de Investigación en Biología Evolutiva (GIBE), the line of research on the evolutionary divergence process in Platyrrhini considering different aspects of the organization of the genome has been established and developed uninterruptedly for more than 30 years. Among the advances made in recent years is the quantification of the genome size in six species of caí monkeys (Cebus sp.) and two species of howler monkeys (Alouatta sp.) and the description of the composition of base pairs in the constitutive heterochromatin regions in the genera Cebus and Ateles. The first descriptions were made of the karyotype and meiotic behavior in early prophase I of two species of howler monkeys, Alouatta caraya and A. guariba clamitans. In this last species, the first pentavalent-type sexual system X1X2X3Y1Y2 was identified in a primate species. The organization of euchromatin was characterized in terms of the content and distribution of AT and GC nucleotide bases in three species of howlers and in two species of caí monkeys. These, among other investigations, allowed contributing in an original way to the knowledge about speciation at different levels, as well as about the architecture and dynamics of the genome of these primates.